Inibição e especificidade da Lbpro do vírus da febre aftosa - Santos, Jorge Alexandre Nogueira [UNIFESP] (2009)
Foot-and-mouth disease virus (FMDV), a global animal pathogen, possesses a single-stranded RNA genome that, on release into the infected cell, is immediately translated into a single polyprotein. This polyprotein product is cleaved during synthesis by proteinases contained within it into the mature viral proteins. The first cleavage is performed by the leader protease (Lbpro) between its own C-terminus and the N-terminus of VP4. Lbpro also specifically cleaves the two homologues of the cellular eukaryotic initiation factor (eIF) 4G, resulting in shut-off of host capdependent mRNA translation. Consequently, FMDV RNA, which initiates translation via IRES, and does not require intact eIF4G, can freely use the host protein synthesis machinery for viral protein synthesis. We used a panel of specifically designed fluorogenic peptides to examine the substrate specificity, effects of pH and ionic strength on Lbpro activity and of its shorter mutant sLbpro. Compared with other cysteine peptidases, how papain and the cathepsins, Lbpro and sLbpro possesses several unusual characteristics, including a high sensitivity to salt and a very specific substrate binding site extending up to P7. Indeed, almost all substitutions investigated were detrimental to Lbpro and sLbpro activity. Analysis of structural data showed that Lbpro binds residues P1 to P3 in an extended conformation whereas residues P4 to P7 are bound in a short 310 helix. The specificity of Lbpro as revealed by the substituted peptides could be explained for all positions except P5.